Scheduling algorithms to support QoS and service integration in sensor and actuator networks - Cabral, José (2006)
In this paper we analyse and evaluate several Scheduling Algorithms that are candidates to support Quality of Service and Service Integration in Sensor and Actuator Networks. They should satisfy two main goals: to guarantee committed delays for time sensitive services, and to improve the network transmission efficiency. The algorithms are described and some results, obtained by simulation, are presented. The proposed Traffic Class Oriented Algorithm proved to be a good solution to meet the proposed objectives as well as to integrate traffic generated by Fieldbus devices and control applications in real communication networks.